-5/6x-1/9x=2

Simple and best practice solution for -5/6x-1/9x=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5/6x-1/9x=2 equation:



-5/6x-1/9x=2
We move all terms to the left:
-5/6x-1/9x-(2)=0
Domain of the equation: 6x!=0
x!=0/6
x!=0
x∈R
Domain of the equation: 9x!=0
x!=0/9
x!=0
x∈R
We calculate fractions
(-45x)/54x^2+(-6x)/54x^2-2=0
We multiply all the terms by the denominator
(-45x)+(-6x)-2*54x^2=0
Wy multiply elements
-108x^2+(-45x)+(-6x)=0
We get rid of parentheses
-108x^2-45x-6x=0
We add all the numbers together, and all the variables
-108x^2-51x=0
a = -108; b = -51; c = 0;
Δ = b2-4ac
Δ = -512-4·(-108)·0
Δ = 2601
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{2601}=51$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-51)-51}{2*-108}=\frac{0}{-216} =0 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-51)+51}{2*-108}=\frac{102}{-216} =-17/36 $

See similar equations:

| (b/7)+(1/4)=19 | | 31+119+x=150 | | -3.4+v/5=-15.9 | | 4(x-6)+4=6x+2(x-6) | | –(7x–2+12)+(-5x–3x+4)=–(-x+7)–(6x–4–7) | | 6(-3)+3y=9 | | 2x2+19x+9=0 | | 2=3x=19/5 | | 2x+7-24=100+4x | | 5(x-2)+6x=7x+4(x-6) | | s/9+26=29 | | –11g=18−20g | | N2/5+2n/6=12 | | (5x-15)+(8x-8)=180 | | 16d=14d+18 | | m/7+40=46 | | 186-w=232 | | 6(9+x)=54 | | 9000m=2700 | | 2x2+x+1=0 | | 5s-4s=17 | | 16=b/7+13 | | 7x–10x=9 | | b+13/4=9 | | -(18-4x)=18 | | 17x=-51;x=-3 | | 85=9d+4 | | 9(k+1)=90 | | 5^n=5^11⋅5^3 | | 4x=4x-4+2x | | 5^n=56^11⋅5^3 | | -19+8s=-91 |

Equations solver categories